Women, work and motherhood: the balancing act: a study of white middle-class women - Lawes, Ginny. (1993)
The thesis was basically exploratory in nature. A staged life cycle model, with three key stages, was developed which jointly incorporated women's work and motherhood roles. The chosen stages led to a focus on white middle-class women. This was therefore the target group from which the samples were drawn and the focus of any generalisation from these studies. The primary focus of the work was on the decision-making processes that women go through in making the transition from one stage to the next. This was looked at in terms of a cost/benefit model that incorporated meaning through an exploration of the stresses and satisfactions that women experienced at the three identified stages. This allowed the initial decision-making model to be 'unpacked', and the relevant factors to be identified. These were considered in detail and looked at in the context of the relevant literature. One factor, role conflict, was explored further in a separate survey where roles were found to be potential sources of support as well as of demands. In looking at the decision to return to work, five factors were found to be particularly important to the women, and these were successfully checked for reliability in a separate study. The research was started in 1986, and the surveys were undertaken in 1987 and 1988.